Babilonia: entre el mito y la realidad - Carvajal Mena, Ligia (2016)
This article aims to highlight the importance of the Babylonian culture in the history of humanity, especially for the Hebrew and Greek culture. Babylon, between myth and reality, was able to develop a series of cultural events that impacted and struck the Western culture. In the literary field, the works of Homer and Hesiod are an example of this, as well as the development of religious beliefs still feed the societies collective imaginary.In the legal field the code of Hammurabi was essential to support the Despotic State; at present this work also is important for understanding the Juridical Science expressions.